2020
DOI: 10.21203/rs.3.rs-114898/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic Role of DFNA5 in Head and Neck Squamous Cell Carcinoma Revealed by Systematic Expression Analysis

Abstract: The gasdermin E gene (GSDME, also known as DFNA5) is mutated in familial aging-related hearing loss. Recent studies have also revealed that the expression of DFNA5 is suppressed in many cancer types; however, little is known about the function of DFNA5 in head and neck squamous cell carcinoma (HNSCC). Accordingly, the aim of the present study was to evaluate the expression of DFNA5 and explore its prognostic value in HNSCC. We used a set of bioinformatics tools, including Oncomine, TIMER, TISIDB, cBioPortal, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These results demonstrate that CXCR4 expression is downregulated in vitro, suggesting that CXCR4 regulation plays an important role in tumor progression in vivo. In addition, our TGCA analysis of HNSCC samples showed that GSDME overexpression in tumor compared to normal tissue, correlates with worse OS, which may be explained by the reported lack of tumor infiltrated lymphocytes in GSDME + HNSCC tumors by other authors [ 42 ]. Consistently with our results, GSDME overexpression in tumor tissue has also been reported in different cancer types [ 25 , 32 , 43 , 44 ], which contrasts with the assumption that GSDME is silenced in tumors given its tumor suppressor role [ 23 , 24 , 45 – 49 ].…”
Section: Discussionmentioning
confidence: 64%
“…These results demonstrate that CXCR4 expression is downregulated in vitro, suggesting that CXCR4 regulation plays an important role in tumor progression in vivo. In addition, our TGCA analysis of HNSCC samples showed that GSDME overexpression in tumor compared to normal tissue, correlates with worse OS, which may be explained by the reported lack of tumor infiltrated lymphocytes in GSDME + HNSCC tumors by other authors [ 42 ]. Consistently with our results, GSDME overexpression in tumor tissue has also been reported in different cancer types [ 25 , 32 , 43 , 44 ], which contrasts with the assumption that GSDME is silenced in tumors given its tumor suppressor role [ 23 , 24 , 45 – 49 ].…”
Section: Discussionmentioning
confidence: 64%